Phenethyl isothiocyanate and dasatinib combination synergistically reduces hepatocellular carcinoma growth via cell cycle arrest and oxeiptosis - Gabriele Strusi; Caterina M. Suelzu; Nicole Horwood; Andrea E. Münsterberg; Yongping Bao (Frontiers Media S.A., 2023)
Introduction: Hepatocellular carcinoma (HCC) is the most common type of liver cancer, which is among the most lethal tumours. Combination therapy exploits multiple drugs to target key pathways synergistically to reduce tumour growth. Isothiocyanates have been shown to possess anticancer potential and to complement the anticancer activity of other compounds. This study aimed to investigate the potential of phenethyl isothiocyanate (PEITC) to synergise with dasatinib, improving its anticancer potential in HCC.Methods: MTT, 3D spheroids and clonogenic assays were used to assess the combination anti-tumour effect in vitro, whereas a murine syngeneic model was employed to evaluate the combination efficacy in vivo. DCFDA staining was employed to evaluate the production of reactive oxygen species (ROS), while flow cytometry and Western blot assays were used to elucidate the molecular mechanism of the synergistic activiy.Results: PEITC and dasatinib combination exhibited a synergistic effect in vitro and in vivo. The combination induced DNA damage and oxidative stress through the production of ROS, which led to the formation of a premature CDK1/Cyclin B1 complex associated with induction of mitotic catastrophe. Furthermore, ROS activated oxeiptosis, a caspase-independent form of programmed cell death.Conclusion: PEITC showed to enhance dasatinib action in treating HCC with increased production of ROS that induced cell cycle arrest followed by mitotic catastrophe, and to induce oxeiptosis. These results highlight the role that ITCs may have in cancer therapy as a complement of clinically approved chemotherapeutic drugs.